Institution of Islam Java: Coastal Islam, Local Culture, and the Role of Sufism - Nur Syam; Wahyu Ilaihi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
The purpose of this study is to examine the institutionalization of Islam in Java, which is the work of coastal Islamic communities, particularly the envoys or Sufis who collaborated with local coastal traditions. As a result of document studies, it can be seen that the institutionalization of Islam in Java was a long process carried out by envoys spreading Islam. Among the efforts made were through da’wah or the spread of Islam individually by agents of the spread of Islam, and then jointly establishing the kingdom and becoming more structured with the establishment of Islamic educational institutions or pesantren. The Islam produced in this long process is Islam in its acculturative or collaborative style, namely the practice of Islamic teachings in harmony with local traditions. Even though there have been changes for the sake of change, the principal teachings in Islam have not changed except for teachings that are instrumental in nature. One of the greatest attributes in the process of coastal Islamization is the creation of understanding and practice of religion in a moderate style.